Quantitative determination of completeness of mastering scientific concepts in learning geography - Чудіна, Ольга Леонідівна (Educological discourse, 2014)
The article is devoted to the problem of determination of completeness of mastering scientific concepts during student geographers are acquiring them. An author specified the basic coefficients of plenitude of mastering of separate logical component concepts, on the basis of complex estimation of them the levels of formed geographical concepts are developed according the Bologna-process requirements.